Habituation of Character Education at The Aisyiyah Orphanage in Banua Anyar - Uswatun Isnaini; Ersis Warmansyah Abbas; Jumriani Jumriani (Universitas Lambung Mangkurat, 2023)
The Orphanage is a social service institution established by the government and the community, which aims to help or provide assistance to individuals and community groups to meet life's needs. Habituation is seen in the child's attitude contained in character education. This article aims to describe the habituation of character education of Aisyiyah Orphanage in Banua Anyar Village as social welfare responsible for providing substitute services in meeting its foster children's physical, mental, and social needs. The training activities were implemented in 2 days, namely on Saturday, November 20, 2021 and Thursday, November 25, 2021, which children at the Banua Anyar Village Orphanage attended. The activity provides training that focuses on character-building to children. The method used in this training activity is the Lecture Method, the method aims to provide information about Character Education that can be taken from daily activities. The process of forming Character Education in children is packaged in the form of training by instilling character education through activities carried out daily. Training is designed in 2 stages, namely, 1) the stage of delivering material using the lecture method, and 2) the stage of implementing training that has been designed to instill Character Education in children. The result of the training became a dedication in the world of education in providing an experience for the nation's generation with character as a form of social concern for the scope of education from the IPS FKIP ULM Education Study Program institution.